Chapter The offshore environmental impact by Sarno river in Naples bay (South-West Italy) - Di Leo, Antonella (Proceedings e report, 2020)
The goal of this work has been to establish the influence of the Sarno river on the present sedimentation in the Naples bay continental shelf by evaluating organic matter contribution and pollution. Sediments samples were collected, by van Veen grab, in 71 stations located offshore the Sarno river between Vesuvian and Sorrento Peninsula coasts. The characteristics of the surface sediments were analysed to highlight spatial trends in the (i) granulometry (grain-size); (ii) total nitrogen, organic carbon and total phosphorus; (iii) metal content (Hg, Cd, Pb, As, Cr, Cu, Ni, Zn, Fe and Mn).